Comprehensive Integrity Assessment Framework for Ageing Offshore Platforms in Tropical Marine Environments: An Integrated Approach Combining SHM, Probabilistic Analysis, and Digital Twin Technology - Mutadi, Mutadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This comprehensive study presents an advanced integrated framework for assessing the structural integrity of ageing offshore platforms operating in tropical marine environments. The framework synergistically combines stateoftheart Structural Health Monitoring (SHM) systems, contemporary metocean data analysis, sophisticated probabilistic reliability assessment methodologies, and cuttingedge digital twin implementation. Over an extensive 18month monitoring period conducted on a representative ageing offshore platform, critical findings emerged: contemporary environmental loads exceeded original design specifications by 1525%, splash zone corrosion rates reached 0.32 mm/year (approximately 160% of design assumptions), and reliability indices for ultimate strength under operating conditions ranged between 2.62.9, below the ISO 19902 target of 3.0. The implemented digital twin system demonstrated exceptional performance with 94% accuracy in stress prediction during extreme weather events and enabled realtime visualization of structural behavior. This research provides a scientifically rigorous, datadriven foundation for life extension decisions and optimized maintenance strategies for ageing offshore infrastructure in tropical regions, representing a significant advancement over conventional assessment methodologies.